Fisioterapia baseada em evidências após Acidente Vascular Encefálico: adaptação transcultural do questionário Practitioner and Organizational Barriers to Evidence-based Stroke Rehabilitation e identificação das barreiras práticas e organizacionais - Maria Oliveira Paixão Fernandes (2017)
The objective of the present study is to identify the main barriers to the practice of evidence-based physical therapy for individuals with stroke by applying the "Practitioner and Organizational Barriers to Evidence-based Stroke Rehabilitation questionnaire", translated and adapted to Portuguese - Brazil. One hundred sixty four Brazilian physiotherapists who attended patients after stroke. This exploratory cross-sectional study was carried out in two phases: Phase I consisted of translation and cross-cultural adaptation of the questionnaire "Practitioner and Organizational Barriers to Evidence-based Stroke Rehabilitation", originally in English, for Portuguese -Brazil, according to transcultural translation and adaptation guidelines reported in the literature. Phase II consisted of the application of the final version of the instrument translated to a sample of Brazilian physical therapists who performed care for individuals after stroke, to determine the barriers to EBP implementation. The questionnaire was translated into Portuguese-Brazil from the semantic, cultural and conceptual point of view. A total of 88.7% of respondents agreed that EBP application is required, 60% agreed that EBP imposes excessive demands on physical therapists, and 93.8% were interested in improving the skills needed to incorporate EBP into practice. 90.4% of physical therapists were in a workplace that did not require the use of current research results in clinical practice and 72.4% did not have access to current research in the workplace. Mean scores between 60 and 80% were reported in relation to the confidence in critically analyzing the literature regarding reliability and relevance. Mean scores below 60% were reported for items interpreting results from statistical procedures such as linear regression or logistic regression and interpreting results from statistical procedures such as t-tests and chi-square. The four main barriers pointed out by the interviewees were insufficient time, lack of generalization of research results regarding the patient population, lack of understanding of statistical analyzes and lack of support among co-workers. There is a need to improve organizational resources to increase the use of EBP in care for patients in rehabilitation after stroke. The workplace should support the use of PBE